2022
DOI: 10.3389/fpsyg.2022.992575
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of mindfulness-based interventions on empathy: A meta-analysis

Abstract: Empathy is essential for human survival and social interaction. Although mindfulness-based interventions (MBIs) have been used to improve empathy in healthy populations, its therapeutic efficacy remains unknown. This study aims to investigate the therapeutic effects of MBIs on empathy in a healthy population and the potential factors affecting the efficacy of MBIs. The literature search focused on PubMed, Embase, Web of Science, Cochrane Library, and CNKI from inception to September 2022. Randomized controlled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…We found that affective empathy could moderate the relationship between two symptoms of aggression and PSU: “productivity loss” and “physical aggression”. Therefore, individuals can employ psychological counseling techniques and skills, such as mindfulness ( 59 ), which have been demonstrated to effectively enhance empathy, to address the relationship between PSU and aggression. In sum, the present study suggests that the mechanism of PSU may be different among adolescents with different levels of empathy, and studies to further clarify the underlying mechanism of PSU are still warranted.…”
Section: Discussionmentioning
confidence: 99%
“…We found that affective empathy could moderate the relationship between two symptoms of aggression and PSU: “productivity loss” and “physical aggression”. Therefore, individuals can employ psychological counseling techniques and skills, such as mindfulness ( 59 ), which have been demonstrated to effectively enhance empathy, to address the relationship between PSU and aggression. In sum, the present study suggests that the mechanism of PSU may be different among adolescents with different levels of empathy, and studies to further clarify the underlying mechanism of PSU are still warranted.…”
Section: Discussionmentioning
confidence: 99%
“…It also has a positive relationship with the occurrence of anxiety and depressive disorders [68]. The practice of mindfulness has a positive impact on maintaining the body's homeostasis [69], emotional stability [70], increasing empathy [71], reducing anxiety, and regulating the functioning of the sympathetic nervous system [72]. Mindfulness is a safe method, and the overall rate of adverse events is 8.3% [73].…”
Section: Mindfulnessmentioning
confidence: 99%
“…Another recent systematic review focused exclusively on the effectiveness of mindfulness-based interventions on empathy in healthy populations and included 12 randomized clinical trials and 1 quasi-experimental study[ 28 ]. Its meta-analysis found a statistically significant positive standardized mean difference of 0.37 (95% confidence interval: 0.16 to 0.58) favoring the mindfulness-based interventions in improving empathy levels in comparison to controls.…”
Section: Introductionmentioning
confidence: 99%